An ethnographic study of people’s strategies to avoid food waste - Reyes Cruz, Aurea Gisela (2016)
Disturbing volumes of food waste generation around the world have been recently reported. The Food and Agriculture Organization of the United Nations (FAO, 2011) estimate that one third of food is wasted or lost each year worldwide. It has also been reported that in developed countries about half of food waste generated in a year comes from households (Quested & Parry, 2011). Although government policies and campaigns have been created to reduce these amounts, very little has been done to thoroughly understand the practices and activities that trigger the generation of food waste inside households, and the strategies that are presently used to avoid it. This study investigated such strategies through an ethnographic study of three different households conducted for three weeks, carrying out fieldwork combined with semi-structured and contextual interviews, diaries and instant messaging. Many strategies to avoid food waste were identified within ordinary activities related to food such as shopping, storing, preparing, cooking, eating and discarding. Important factors to accomplish such strategies, and possible areas to be supported by technology, were ascertained through analysis. A set of design requirements were generated informed by the study findings and ultimately a paper-based prototype of a mobile application was designed based on the requirements and evaluated. The results showed that there are commonalities among households influencing food waste and its avoidance, but at the same time exposed the need to design systems with flexibility, acknowledging that households may have different needs and different types of users. These are the factors designers and developers must take note of, because they are the key point to reduce food waste in households.